Spatial clustering in low density circumstances: Industrial specialisation by region in two Nordic countries - Heikki Eskelinen; Kimmo Niiranen (European Regional Science Association (ERSA), 1998)
Specialisation is considered to be an important competitive strategy not only in individual firms, but also at a regional level. Increasingly, the spatial clustering of similar or related industrial activities is argued to derive from the inter-firm interaction which contributes to a creation of new knowledge and other unique resources embedded in certain places, regions or countries. Obviously, spatial conditions for knowledge creation, and consequently, for upgrading competitiveness through inter-firm learning, vary considerably. The present paper focuses on Finland, Sweden and Norway, which are characterised by low population densities and scattered settlement structures. In these countries, most functional regions (e.g., labour market districts) can be argued to be too small to accommodate a specialised industrial cluster benefiting from economies of scale and scope. On the other hand, many regions with a sufficient volume of economic activities tend to be too large in area to create a seedbed for specialised growth relying on inter-firm interaction on a daily basis. In the present paper, the above outlined issues are investigated on the basis of a large data set which covers industrial activities disaggregated by regions and by sectors from the 1970s to the 1990s. The three Nordic countries are compared, and spatial clustering is analyzed using various regional classifications. In addition, reasons for specialised growth such as natural resource base, local learning processes, and R&D inputs are surveyed.
Keywords: 330